The Conflict Between Tradition And Modernity - Balasundaram, S N (Journal of Dharma, 1986)
The desire for a common civil codé in India is a thrust towards modernity in a traditional society which seeks to weld the mutually exclusive communal and religious groups into a united and viable society. It is a laudable but difficult attempt at laying the foundations of secularism which is envisaged by our Constitution and, in the context of a religiously pluralistic society, means an equal respect to all religions, though this is not the meaning in which westerners understand the concept. The process of modernizing the Indian society began with the establishment of the British imperial rule in the old Indian dependency when the alien rulers introduced the Westren liberal ideas of administration end politics with which they had been familiar. The Cornwallis Code of 1793 was the first deliberate administrative effort on the part of the British to grant civil rights of property and persons to all Indian subjects without any religious or communal distinction. This process of bringing the Indians of different religious persuasions under a common civil and criminal law continued during the British rule. The Civil Procedure Code, the Criminal Procedure Code, the law of contract, tort and evidence and the Indian Penal Code are the imperialist legacy to free India , and they constitute the base of a common civil and criminal code in free India that makes no distinction between a Hindu or a Muslim, or a Christian, or a Parsee in the administration of justice. In other words, equality before law which our Constitution enshrines is the priceless gift of the British rule. It was unknown both to the Hindus of ancient India who observed inequality based on the differences of caste (varnabêda), and to the Muslims of mediaeval India who regarded the non-Muslims (zimmis) as second-class citizens.